One-month changes in blood pressure-adjusted pulse wave velocity for predicting long-term cardiovascular outcomes in patients undergoing percutaneous coronary intervention. Issue 3 (27th March 2023) - Kim, Hack-Lyoung; Joh, Hyun Sung; Lim, Woo-Hyun; Seo, Jae-Bin; Kim, Sang-Hyun; Zo, Joo-Hee; Kim, Myung-A
Abstract : Objective: The prognostic value of changes in arterial stiffness has not been well evaluated. This study was conducted to investigate whether the change in arterial stiffness one month after percutaneous coronary intervention (PCI) affects the long-term cardiovascular prognosis. Methods: A total of 405 patients (mean age, 62.0 ± 11.0 years; female sex, 27.7%) who underwent PCI with drug-eluting stent (DES) implantation was prospectively enrolled. The measurement of brachial-ankle pulse wave velocity (baPWV) was taken in all the study patient at the time of admission for index PCI. Major adverse cardiovascular event (MACE), a composite of cardiac death, nonfatal myocardial infarction, coronary revascularization and ischemic stroke, was assessed during clinical follow-up after index PCI. Results: During the median follow-up duration of 5.3 years (interquartile range. 2.9–7.9 years), there was 65 MACE (16.0%). There was no significant difference in clinical characteristics between patients with and without MACE except for higher prevalence of triple vessel disease in those with MACE. The baPWV value decreased at one month after index PCI (1560 ± 305 to 1530 ± 318 cm, P  < 0.001). In multivariable cox regression analysis, the change of baPWV at one month was not associated with MACE occurrence ( P  > 0.05). However, the change in systolic blood pressure (SBP)-adjusted baPWV (baPWV/SBP) at one month (increased vs . decreased) was significantly associated with MACE occurrence even after controlling for potential confounders (hazard ratio, 2.25; 95% confidence interval, 1.37–3.69; P  = 0.001). Conclusion: The baPWV/SBP change at one month was associated with long-term MACE in patients undergoing DES implantation. The results of this study suggest that baPWV/SBP changes at one month may be helpful in risk stratification of patients at a high coronary risk.